2021
DOI: 10.1186/s12955-021-01666-3
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of fertility quality of life and the influencing factors of patients with repeated implantation failure

Abstract: Background The objective of this study was to investigate the current status of fertility quality of life (QoL) and explore the influencing factors for infertile women with repeated implantation failure (RIF). Methods The sample consisted of 137 infertile women with RIF who were under treatment from January 2019 to December 2019 in the Reproductive Medical Center of Ruijin Hospital, affiliated with Shanghai Jiaotong University School of Medicine in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 40 publications
5
19
0
1
Order By: Relevance
“…Infertile women undergoing repeated IVF-ET cycles often bear the dual pressures of family and society and have varying degrees of psychological problems. Additionally, in our previous study, we found that the anxiety and depression of patients with repeated implantation failure has significantly affected fertility quality of life [ 33 ]. In the process of treatment, negative emotions often affect the outcomes of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Infertile women undergoing repeated IVF-ET cycles often bear the dual pressures of family and society and have varying degrees of psychological problems. Additionally, in our previous study, we found that the anxiety and depression of patients with repeated implantation failure has significantly affected fertility quality of life [ 33 ]. In the process of treatment, negative emotions often affect the outcomes of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that there are fundamental differences between Chinese and Western fertility concepts. Infertility patients in China seem to be more influenced by the traditional Chinese saying, “There are three forms of unfilial conduct, of which the worst is to have no descendants” [ 15 ], meaning that it is unacceptable for people not to have offspring. Accordingly, infertility patients can be looked down upon and their families may feel shameful [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The QoL of women with infertility is lower than that of other women of childbearing age (8). Factors that influence the QoL of women with infertility include gender, age, duration of infertility, educational level, marital relationship, fertility expectation, psychological status, and history of assisted pregnancy (8). The quality of life is also one of the main indexes to assess the effects of women and challenges to human fertility arise so health systems have an important role in promoting, maintaining, and rehabilitating people's health and make it possible to achieve optimal health status through good performance and optimal use of available resources (9).…”
mentioning
confidence: 95%
“…The QoL of women with infertility is lower than that of other women of childbearing age (8). Factors that influence the QoL of women with infertility include gender, age, duration of infertility, educational level, marital relationship, fertility expectation, psychological status, and history of assisted pregnancy (8).…”
mentioning
confidence: 99%